How the Principle of Sufficient Reason Undermines the Cosmological Argument - Briceno-Dominguez, J (UNIV FED MINAS GERAIS, DEPT FILOSOFIA & CIENCIAS HUMANAS, 2023)
My aim here is to show how the Cosmological Argument (CA) is undermined by one of its own premises: the Principle of Sufficient Reason (PSR). Firstly, I explain the type of CA that I am thinking about (I). Secondly, I explain a traditional modal objection against the PSR, which is ultimately based upon our intuitions in favor of contingency (II). Thirdly, I show how this modal objection begs the question against the necessitarian, and then I reformulate the CA in more neutral terms (III). Fourthly, using this more neutral version of the CA, I argue that the main problem with the PSR goes way beyond its apparent necessitarian consequences. As an argument used by Bradley shows, embracing the rationalist path that underlies the PSR seems to commit us to a form of Radical Monism too (IV). Finally, I conclude by showing how this result ultimately undermines the CA itself (V).